Super‐wideband multi‐input–multi‐output dielectric resonator antenna. Issue 1 (18th September 2019) - Gotra, Shailza; Varshney, Gaurav; Pandey, Vinay Shankar; Yaduvanshi, Rajveer Singh
Abstract : A half‐split inverted‐frustum shaped two‐port multi‐input–multi‐output (MIMO) dielectric resonator antenna is proposed with the ultra‐wideband response. The antenna provides the impedance bandwidth of 132.69% ( 7 − 34.6 GHz ) with each port. The MIMO performance parameters like envelope correlation coefficient, diversity gain, mean effective gain and channel capacity loss remain in the acceptable limits with the isolation more than 20 dB throughout the operating band. In addition, the antenna provides the peak gain ranging from 4 − 9.5 dBi at port‐1 and 4 − 8 dBi at port‐2.